2020
DOI: 10.3892/etm.2020.9077
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with catalpol protects against cisplatin‑induced renal injury through Nrf2 and NF‑κB signaling pathways

Abstract: Cisplatin (CP) is one of the most widely used chemotherapy drugs for cancer treatment, but it often leads to nephrotoxicity. It is well known that catalpol exhibits antioxidant and anti-inflammatory functions, thus the present study aimed to investigate the potential protective effects of catalpol on CP-induced kidney injury in rats, in addition to determining the underlying mechanisms. Sprague-Dawley rats were treated with 25, 50 or 100 mg/kg catalpol for two days, injected with 20 mg/kg cisplatin and catalpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
(45 reference statements)
1
5
0
Order By: Relevance
“…A recent study about cisplatin-induced renal injury shows that catalpol inhibits cisplatin-induced upregulation of pro-inflammatory cytokine through activating the Nrf2 and inhibiting the NF-kB signaling pathways. 32 As expected, in our study, we found that catalpol significantly decreased proinflammatory cytokine and the expression of p-IKBa and p-65. Taken together, catalpol reduced Ang II-induced renal inflammation through NF-kB signaling pathway.…”
Section: Discussionsupporting
confidence: 89%
“…A recent study about cisplatin-induced renal injury shows that catalpol inhibits cisplatin-induced upregulation of pro-inflammatory cytokine through activating the Nrf2 and inhibiting the NF-kB signaling pathways. 32 As expected, in our study, we found that catalpol significantly decreased proinflammatory cytokine and the expression of p-IKBa and p-65. Taken together, catalpol reduced Ang II-induced renal inflammation through NF-kB signaling pathway.…”
Section: Discussionsupporting
confidence: 89%
“…Liu et al demonstrated that Cat treatment ameliorated psoriatic‐like symptoms through upregulating Sirt1 via blocking NF‐κB, and MAPKs signaling 57 . A former research has implied that Cat may inhibit cisplatin‐induced renal injury and suppress the associated inflammatory response through activating the Nrf2/HO‐1 signaling 58 . Thus, it was assumed that Cat might exert renoprotective effects in SAKI via upregulating Sirt1 and activating Nrf2/HO‐1 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…57 A former research has implied that Cat may inhibit cisplatininduced renal injury and suppress the associated inflammatory response through activating the Nrf2/HO-1 signaling. 58…”
Section: Sirt1 Silence Reverses the Effect Of Cat On Lps-induced Infl...mentioning
confidence: 99%
“…In vivo KI mice Inhibiting NF-κB pathway (Zhang et al [2020]) LPS-induced neurotoxicity (Jiang et al, 2008;Tian et al, 2006), suggesting that catalpol exerts a protective effect on dopaminergic neurons by inhibiting microglia activation and reducing the production of proinflammatory factors. Bi et al pretreated astrocytes with 0.1 mM and 0.5 mM catalpol for 1 h and significantly inhibited NO, ROS, iNOS production, and NF-κB activation in a dose-dependent manner.…”
Section: Acute Kidney Injurymentioning
confidence: 99%
“…Studies have shown that ischemia-reperfusion (IRI)(Gill et al, 2005), angiotensin II (Ang II)(Ruiz-Ortega et al, 2002), and the chemotherapeutic agent cisplatin (CP)(Holditch et al, 2019) can cause AKI. Zhu et al found that catalpol significantly reduced the activity of TNF-α, IL-1β, IL-6, and IL-10 in kidney IRI mice(Zhu et al, 2015).Zhang et al found that catalpol reduced the inflammatory response to kidney injury induced by Ang II and CP by inhibiting the NF-κB signaling pathway(Cong et al, 2022;Zhang et al, 2020). In summary, catalpol attenuates the inflammatory response in kidney injury by inhibiting the NF-κB signaling pathway.3.4.2 | Chronic kidney diseaseThe development of chronic kidney disease is associated with mechanisms such as inflammation and oxidative stress.…”
mentioning
confidence: 99%